Awakening children's minds - Berk, Laura E. (Oxford University Press, 2001)
This is the first book to bring to a general audience, in lucid prose richly laced with examples, truly state-of-the-art thinking about child rearing and early education. Berk's central message is that parents and teachers contribute profoundly to the development of competent, caring, well-adjusted children. In particular, she argues that adult-child communication in shared activities is the wellspring of psychological development. These dialogues enhance language skills, reasoning ability, problem-solving strategies, the capacity to bring action under the control of thought, and the child's cultural and moral values. Berk explains how children weave the voices of more expert cultural members into dialogues with themselves. When puzzling, difficult, or stressful circumstances arise, children call on this private speech to guide and control their thinking and behavior. In addition to providing clear roles for parents and teachers, Berk also offers concrete suggestions for creating and evaluating quality educational environments--at home, in child care, in preschool, and in primary school--and addresses the unique challenges of helping children with special needs